Problem izbire najboljše tajnice - Vidmar, Matija (Obzornik za matematiko in fiziko, 2017)
In the secretary problem we consecutively interview, for a single open position, ?$n \in \mathbb{N}_{\ge 2}$? applicants, with the goal of choosing the best. The decision of whether to reject or accept a given applicant must be made immediately following his interview. For large ?$n$?, approximately, it is optimal to decline the first ?$n/$e? candidates and then to hire the first one that is better than all his predecessors; the best being thus chosen with probability ?$1/e$?. The problem admits a precise and explicit solution for arbitrary ?$n$?.
Keywords: matematika; problemi